Gemcitabine-Vitamin E Prodrug-Loaded Micelles for Pancreatic Cancer Therapy - Miguel Pereira-Silva; Darío Miranda-Pastoriza; Luis Diaz-Gomez; Eddy Sotelo; Ana Cláudia Paiva-Santos; Francisco Veiga; Angel Concheiro; Carmen Alvarez-Lorenzo (MDPI AG, 2024)
Pancreatic cancer (PC) is an aggressive cancer subtype presenting unmet clinical challenges. Conventional chemotherapy, which includes antimetabolite gemcitabine (GEM), is seriously undermined by a short half-life, its lack of targeting ability, and systemic toxicity. GEM incorporation in self-assembled nanosystems is still underexplored due to GEM's hydrophilicity which hinders efficient encapsulation. We hypothesized that vitamin E succinate-GEM prodrug (VES-GEM conjugate) combines hydrophobicity and multifunctionalities that can facilitate the development of Pluronic® F68 and Pluronic® F127 micelle-based nanocarriers, improving the therapeutic potential of GEM. Pluronic® F68/VES-GEM and Pluronic® F127/VES-GEM micelles covering a wide range of molar ratios were prepared by solvent evaporation applying different purification methods, and characterized regarding size, charge, polydispersity index, morphology, and encapsulation. Moreover, the effect of sonication and ultrasonication and the influence of a co-surfactant were explored together with drug release, stability, blood compatibility, efficacy against tumour cells, and cell uptake. The VES-GEM conjugate-loaded micelles showed acceptable size and high encapsulation efficiency (>95%) following an excipient reduction rationale. Pluronic® F127/VES-GEM micelles evidenced a superior VES-GEM release profile (cumulative release > 50%, pH = 7.4), stability, cell growth inhibition (<50% cell viability for 100 µM VES-GEM), blood compatibility, and extensive cell internalization, and therefore represent a promising approach to leveraging the efficacy and safety of GEM for PC-targeted therapies.